Etikalitas Politisi Muda Yang Korup Berdampak Krisis Negarawan - Mic Finanto Ario Bangun; Ratna Indriasari (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2024)
This nation is experiencing a leadership crisis, the rise of young leaders who emerged in the reform era, most of them have the mentality of politicians. Political leadership with a politician's mentality is more calculating about profit and loss, dividing power, securing political power on the other hand. There is no day without news of corruption on various social media, both related to the success of the Corruption Eradication Committee (KPK) in carrying out the Arrest Operation (OTT) and the progress of the trial of the corruption case. done openly. Corruption is like rats that are everywhere, whether in a democracy or a totalitarian political system, rats still exist and continue to breed. Corruption has ensnared government leaders at both the central and regional levels. This descriptive research attempts to answer the question, where has the ethicality of corrupt young politicians, who are public officials, disappeared, resulting in the statesman crisis in Indonesia? The results of this research conclude that the ethicality of corrupt young politicians is lost due to unlimited greed because of the opportunity to come to power without accountability and a lack of statesmanlike reasoning.